Education with Adolescent Pregnancy in Developed and Developing Countries - Arryan Rizqi Aulia Purnamasari (Jurnal Medika Hutama, 2022)
Background: Adolecent pregnancy in early time causes many negative impacts in terms of health, social, and psychological. Adolescent pregnancy is still occurring in developed and developing countries with an increasing trend. 95% of teenage pregnancies occur in low- and middle-income countries. On the other hand, education is a basic thing that can influence the way of thinking as a basis for making someone's decision to act in life, including when teenagers decide to get married or get pregnant. Methods: The research method uses systematic review with journal literature using the online database Pubmed, Science Direct, and Springer Link from 2015-2020. Search keywords used PICO-S (population intervention compare outcome-study design) using Query Education AND Adolescent Pregnancy. There are 8 journals that match the research inclusion criteria. Results: From 8 journal articles analyzed regarding the relationship between education and the incidence of teenage early pregnancy, it can be seen that education can be both a cause and a consequence of adolescent pregnancy. The low level of education of individuals results in low knowledge and cause teenager to have wrong interactions and experience pregnancy. adolescent pregnancy causes teenager to drop out of school and unable to continue their education which will have an impact on their welfare in their future life. Conclusion: Education has a big influence on the incidence of pregnancy in adolescents. A person's educational background will affect the characteristics, behavior, and way of thinking of a person in taking attitudes or actions in his life. the higher the education, the less the incidence of pregnancy in adolescents.